Pediatric radiology casebase - James, Charles A.; Braswell, Leah E.; Glasier, Charles M.; Greenberg, S. Bruce; Seibert, Joanna J. (Thieme, 2015)
Pediatric Radiology Casebase, Second Edition, is a highly anticipated revision of a bestselling board exam review and clinical reference. Each detailed case presentation explains the decision making behind the diagnosis, helping pediatric radiologists and residents easily manage similar cases in their daily practice. Key Features:Almost 700 completely updated, state-of-the-art images accompany the casesSelf-study format allows readers to make their own diagnoses and compare them to the explanations provided with each caseComplete coverage of congenital, developmental, and metabolic disorders as.